The Concept of Social Protection in the Makkan Period: Traditions of Ḥilf and Jiwār and Their Civilizational Significance: A Research Review - Sidra Firdous; Dr. Syeda Saadia (Journal of Religion and Society, 2025)
The Makkan period of the Prophetic mission represents a formative phase in Islamic history, characterized not only by the intellectual and spiritual call toward monotheism but also by acute social vulnerability in the absence of an organized state system. During this period, marginalized groups such as the poor, slaves, travelers, and those without tribal affiliation were frequently exposed to injustice and oppression. In such a socio-political context, Arab society relied on certain non-formal yet effective social mechanisms to ensure protection and justice. Among these mechanisms, the traditions of Ḥilf (collective oath or alliance) and Jiwār (granting of protection or asylum) played a crucial role in maintaining social security. This study explores the concept of social protection in the Makkan era through an analytical examination of the traditions of Ḥilf and Jiwār, highlighting their functional and cultural significance within pre-Islamic Arab society. The research demonstrates how these practices served as ethical frameworks for safeguarding human life, dignity, and property despite the absence of institutional governance. Furthermore, the study underscores the Prophet Muhammad’s ﷺ acknowledgment of these positive social traditions, reflecting Islam’s approach of reforming and universalizing existing moral values rather than negating them entirely. The findings suggest that the Makkan model of social protection offers valuable insights for addressing contemporary issues of social justice, communal responsibility, and the protection of vulnerable groups. ​Keywords: Social Protection, Makkan Period, Traditions of Ḥilf, Jiwār, Civilizational Significance